Evaluation of Corporate Governance Measures: An Application to the Australian Higher Education Sector - De Silva , Chitra; Armstrong , Anona (Journal of Law and Governance, 2012)
Governance has emerged as a major concern in the higher education sector. Although evaluation of performance of governance is widely used in the private and public sectors, little attention has been given to the assessment of good governance practices in university contexts. The purpose of this paper was to describe the changes in government policy associated with the introduction of Governance Protocols that have impacted on the higher education sector and to answer the research question: do Australian Universities apply the best practice corporate governance measures?. Data for the study were compiled from annual reports and the Web pages of 37 publically funded universities in Australia and Selected Higher Education Statistics Collection. The assessment criteria were derived from the National Governance Protocols. Findings revealed that Australian universities as independent corporations apply the universal best practice corporate governance indicators as governance measures.